FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR MAHASISWA JURUSAN AKUNTANSI SEBAGAI AKUNTAN PUBLIK (STUDI KASUS PADA MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS AL WASHLIYAH MEDAN) - YURMAINI, YURMAINI (Fakultas Ekonomi dan Bisnis Islam, 2019)
The purpose of this study was to determine whether the work environment, professional recognition, professional training, and social values ​​influence the career selection to become a public accountant. This research is included in the type of descriptive research with a quantitative approach. The primary data collection method is carried out using a questionnaire method that is distributed to respondents. The population in this study was the Accounting Department Students of the Faculty of Economics, University of Al Washliyah, Medan in 2014, amounting to 30 respondents. The results of this study are as follows: a) T test results can be seen that the work environment variable obtains the value of t-count> t-table = (2.548> 1.696) with a significance value of 0.016 <0.05, then H1 is accepted. This means that the work environment has a positive effect on perceptions of students majoring in career accounting to become public accountants. b) T test results can be seen that the professional recognition variable gets the value of t-count> t-table = (3.921> 1.696) with a significance value of 0.000 <0.05, then H2 is accepted. This means that income perceptions have a positive effect on perceptions of students majoring in career accounting into public accountants. c) t test results can be seen that the professional training variable obtains the value of t-count> t-table = (2.630> 1.696) with a significance value of 0.013 <0.05, then H3 is accepted. This means that the professional training factor has a positive effect on perceptions of students majoring in accounting as careers to become public accountants. d) The results of the t test on the variable social values ​​get the value of t-count> t-table = (2.404> 1.696) with a significance value of 0.022 <0.05, then H4 is accepted. This means that social values ​​have a positive effect on the interests of students majoring in accounting career to be public accountants.